Failure of parathyroid hormone antagonists to inhibit in vitro bone resorbing activity produced by two animal models of the humoral hypercalcemia of malignancy. - D'Souza, S M (1984)
The humoral hypercalcemia of malignancy (HHM) is caused by tumor cells that release a circulating factor which stimulates osteoclastic bone resorption. Recently, it has been reported that tumors associated with HHM contain factors that stimulate renal and bone cell adenylate cyclase. The activity was inhibited by parathyroid hormone (PTH) antagonists, and this led to the hypothesis that hypercalcemia is due to bone resorbing factors that engage PTH receptors in bone. Since it is not known whether the bone resorbing factors act via PTH receptors in bone, we examined the effects of PTH antagonists on PTH-stimulated bone resorption and bone resorbing activity that was produced by two tumor models of HHM which also release these adenylate cyclase stimulating factors. The PTH antagonists [8,18norleucine, 34tyrosine]bovine PTH (3-34) amide and [34tyrosine]bovine PTH (7-34) completely inhibited PTH-stimulated bone resorption. Neither antagonist inhibited bone resorption that was stimulated by the conditioned medium from cells that were derived from the Walker rat 256 tumor model of HHM. Both antagonists also failed to inhibit bone resorption that was stimulated by culture media from cells that were derived from the rat Leydig cell tumor. These data suggest that in these two models of HHM, the bone resorbing factors do not exert their effects by interacting with PTH receptors on bone.